The solidarity sector and its integral Development - Pineda - López, Kelly Lorena; Moreno - Mendoza, Edward Fabian (Universidad Francisco de Paula Santander, 2019)
The solidarity economy in Colombia, is characterized by advancing and creating transformations to the territory through cooperation and mutual aid, for this reason, the study focused on knowing the main causes or problems that affect to promote the solidarity exercise in the territory, through a quantitative methodology of descriptive type to the associations of the municipality of Ocaña, it is concluded that more than 50% of the entities promote innovation and attend the main problem of unemployment and social support to population in condition of extreme poverty.